SPE Production Operations Symposium 1989
DOI: 10.2118/18881-ms
|View full text |Cite
|
Sign up to set email alerts
|

Clay Stabilization in Low-Permeability Formations

Abstract: Clay stabilizers have been used in various forms in oil well treating solutions for over 30 years. Cationic organic polymers have been the most popular type stabilizer in use recently because of their resistance to wash-off and chemical attack, ease of application, and effectiveness in moderate to high permeability formations. Recent studies investigating the effectiveness of such stabilizers in very low to low permeability sandstones have shown them to be less than 100% effective in stabilizing clays to preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Furthermore, some other scientists reported that high molecular weight polyamines are found to block permeability (R.E. Himes, Vinson, and Simon 1991;Zhou, Gunter, and Jonasson 1995;Schlemmer et al 2003). According to Beihoffer et al, combination of quaternary amine with potassium chloride provides greater shale recoveries than with either component alone.…”
Section: Amine Fixationmentioning
confidence: 99%
“…Furthermore, some other scientists reported that high molecular weight polyamines are found to block permeability (R.E. Himes, Vinson, and Simon 1991;Zhou, Gunter, and Jonasson 1995;Schlemmer et al 2003). According to Beihoffer et al, combination of quaternary amine with potassium chloride provides greater shale recoveries than with either component alone.…”
Section: Amine Fixationmentioning
confidence: 99%
“…However, it has been shown that these stabilizers are less effective in low-permeability formations [64]. Most additives used are highmolecular-weight cationic organic polymers.…”
Section: Clay Stabilizersmentioning
confidence: 99%
“… 16 Himes pointed out that an organic cationic polymer clay stabilizer with high RMM could plug the pore throat within the low-permeability reservoir. 17 Wang pointed out that a cationic polymer clay stabilizer with high RMM may block the pore throat and reduce permeability by 70–80% when injected into low-permeability reservoirs. 18 Ma believed that although a cationic polymer clay stabilizer with high RMM can effectively inhibit the water-sensitivity damage for reservoirs with large clay content and low permeability, it would plug the pore throat and increase the plugging damage to reservoir permeability at the same time.…”
Section: Introductionmentioning
confidence: 99%